Determination of genotoxic alkyl methane sulfonates and alkyl paratoluene sulfonates in lamivudine using hyphenated techniques - N.V.V.S.S. Raman; A.V.S.S. Prasad; K. Ratnakar Reddy; K. Ramakrishna (Elsevier, 2012)
Two highly sensitive methods for the determination of genotoxic alkyl methane sulfonates (AMSs) and alkyl paratoluene sulfonates (APTSs) in lamivudine using hyphenated techniques have been presented. AMSs were determined by GCâMS method using GSBP-INOWAX (30Â mÃ0.25Â mmÃ0.25Â Î¼m) column. Temperature program was set by maintaining at 100Â Â°C initially for 3Â min, then rised to 220Â Â°C at the rate of 15Â Â°C/min and maintained at 220Â Â°C for 16Â min. N,N-dimethyl formamide was used as diluent. APTSs were determined by LC-MS using Zorbax, Rx C8, 250Â mmÃ4.6Â mm, 5Â Î¼m column as stationary phase. 0.01Â M ammonium acetate is used as buffer. The mixture of buffer and methanol in 75:25 (v/v) ratio was used as mobile phase A and mixture of buffer and methanol in 5:95 (v/v) ratio was used as mobile phase B. The gradient program (T/%B) was set as 0/28, 16/50, 17/100, 23/100, 27/28 and 40/28. Both the methods were validated as per International Conference on Harmonization guidelines. Limit of quantitation was found 1.5 Î¼g/mL for AMSs and was in the range of 1.0â1.5Â Î¼g/mL for APTSs. Keywords: Genotoxins, Alkyl methane sulfonates, Alkyl paratoluene sulfonates, Lamivudine, Hyphenated techniques